Efficient catalytic activity of BiVO4 nanostructures by crystal facet regulation for environmental remediation. (February 2022) - Srinivasan, N.; Anbuchezhiyan, M.; Harish, S.; Ponnusamy, S.
Abstract: Controlled growth of BiVO4 nanostructures along (121) and (040) crystal facets plays a crucial role in enhancing their catalytic performance. In this regard, the visible light active photocatalyst BiVO4 was synthesized concerning the effect of pH and surfactants by hydrothermal method. The morphology and size of BiVO4 are strongly dependent on the concentration of H + and Bi 3+ in the reaction system while varying the pH. Further, the significant role of cationic surfactant for obtaining the morphology of the spherical nanoparticles of BiVO4 powders with size 55 nm was analyzed. Adsorption behavior of as-synthesized samples was investigated through Langmuir isotherm model. The catalytic performance of BiVO4 photocatalyst with the degradation efficiency of 98.79% and 15.58% over the methylene blue (MB) and methyl orange (MO) dyes were noticed within 60 min of light irradiation respectively. The enhanced and declined catalytic activity was well correlated with the surface charge of BiVO4 photocatalyst towards the MB and MO dyes respectively. Further, the photocatalytic activity of mixed anionic and cationic dyes was performed. The degradation pathway of MB dye was analyzed by LC-MS for the identification of intermediate products. From the obtained results, the proposed possible photocatalytic mechanism reported. Graphical abstract: Image 1 Highlights: The morphology of BiVO4 strongly depends on the concentration of H + and Bi 3+ . XRD, Raman confirms the well crystalline structure of pure monoclinic BiVO4 . Cationic surfactant CTAB play a key role for obtaining the controlled size of BiVO4 . Superior catalytic activity correlates with increase of (040)/(011) intensity ratio. h + and radicals are predominant oxidative species in the dye degradation process.